2020
DOI: 10.6017/ijahe.v7i1.10902
|View full text |Cite
|
Sign up to set email alerts
|

Continuous professional development and student support in an open and distance e-learning institution: a case study

Abstract: Faced with emerging technologies and a diversity of students entering higher education in South Africa, lecturers must continuously equip themselves with the necessary skills to teach and support today’s learners effectively. This article reports on the lessons learnt and experiences of academics at an open distance learning (ODL) institution who participated for the first time in the fully online teaching and learning programme at an international institution, through a partnership aimed at developing academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…and for staff to have access to continuous professional development experiences which equip them with the necessary skills to be so (Modise 2020), as well as access to and training in the use of a variety of technologies for different purposes and contexts (Njoki 2021), research related to adaptation seems to be largely limited to support for learners with disabilities (Zongozzi 2020) or the ways in which learning analytics could be used to 'personalise' a learning experience (Bart et al 2019). The search did not find examples of research which reported on ways in which a programme of study, its contents, its technology choices, and/or its pedagogy had been adapted from the outset and/or during implementation, in response to the wide diversity of learners who might be attracted to distance or online study, especially in provision which is offered across state or national boundaries.…”
Section: Adaptationmentioning
confidence: 99%
“…and for staff to have access to continuous professional development experiences which equip them with the necessary skills to be so (Modise 2020), as well as access to and training in the use of a variety of technologies for different purposes and contexts (Njoki 2021), research related to adaptation seems to be largely limited to support for learners with disabilities (Zongozzi 2020) or the ways in which learning analytics could be used to 'personalise' a learning experience (Bart et al 2019). The search did not find examples of research which reported on ways in which a programme of study, its contents, its technology choices, and/or its pedagogy had been adapted from the outset and/or during implementation, in response to the wide diversity of learners who might be attracted to distance or online study, especially in provision which is offered across state or national boundaries.…”
Section: Adaptationmentioning
confidence: 99%
“…The guidelines of UDL emphasise inclusivity, equity and support to ensure access to all students, without compromising the quality of learning (Behera, 2021).While the extraordinary growth in the use of technology in education has provided many opportunities, it also poses challenges that are still evolving in the face of the realities created by the COVID-19 pandemic. Modise (2020) argues that the diverse nature of the student population and the need to satisfy their demands and support them require further research.…”
Section: Literature Review Student Support Inclusion and Equitymentioning
confidence: 99%
“…However, irrespective of the technology chosen by an institution to deliver education, it is important to design accompanying support strategies that will ensure that the students successfully achieve the intended academic standards. In order to achieve this, lecturers also need the relevant support and training from their institutions (Modise, 2020). It is also important to note that incorporating OER into e-portfolios in HE and DE in developing countries can benefit learners where financial resources are lacking.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%